Collaborative reflection on environmental practices: a vehicle for environmental education in teacher education. Issue 2 (4th March 2022) - Kalsoom, Qudsia; Khanam, Afifa; Qureshi, Naima
ABSTRACT: Environmental education and sustainability education have emerged as a key focus in teacher education in the past few decades. Researchers have investigated the impact of different pedagogies on pre-service teachers' sustainability or environmental consciousness. The current study was an attempt to investigate the impact of collaborative reflection (focusing on environmental issues and practices) on pre-service teachers' environmental practices. Forty-six pre-service teachers participated in the study. The data were gathered qualitatively through field notes and participants' written reflections. The findings indicated that collaborative reflection on environmental issues and practices promote pro-environmental practices among the participants. The study suggests the use of collaborative reflection on environmental issues and practices as a pedagogy for environmental education in teacher education.